Decision Support System Direct Cash Assistance Of Village Funds (Blt Dd) Using Weighted Aggregated Sum Product Assement Waspas Method (Case Study Of Padang Pandan Village) - Suci Permata Sary; Herlina Latifa Sari; Dewi Suranti (Jurnal Media Computer Science, 2023)
The problems found in this study are how to make a Decision Support System application for direct cash assistance to BLT DD village funds by applying the Waspas method to Padang Pandan Village. Decision Support System is an information system that provides information, modeling and data manipulation. Decision support systems provide specific interactive support for the decision-making process of managers and other business practitioners. The purpose of the Decision Support System is to make it easier to collect data on the implementation of BLT village funds.The WASPAS method is a combination of two methods, namely the WSM (Weight sum model) and the Weight product model (WPM). WSM is a weighted quantity, while WPM is a weighted product model. So it can be defined that WASPAS is an assessment of the weighted aggregate amount product. The results of the study that the waspas method can collect data on the value of the results of information calculations about direct cash assistance for BLT DD village funds in Padang Pandan village